Exploring the Value of Interprofessional Collaboration between Occupational Therapy and Design: A Pilot Survey Study - Amy Wagenfeld; Lori Reynolds; Tamar Amiri (Scholarworks @ WMU, 2017)
Background: Consistent with the American Occupational Therapy Association's Vision 2025, interprofessional partnerships between occupational therapy and designers is necessary to "maximize health, well-being, and quality of life for all people . . . through effective solutions that facilitate participation in everyday living" (2016, para 1). Occupational therapy's knowledge of the person-environment-occupation fit appears to make us well suited to collaborate with design teams to create environments that facilitate optimal function and promote health and well-being (Ainsworth & de Jonge, 2014). Method: Two short closed-ended online questionnaires were designed to gain an understanding of designer and occupational therapy practitioner impressions of interprofessional collaborations between occupational therapy practitioners and designers. Results: Domestically and internationally, 224 occupational therapy practitioners and 127 designers completed the questionnaires. The results indicate current barriers to collaboration among occupational therapy practitioners and designers are due to different professional languages, a lack of opportunity to interface, and designers not fully grasping the scope of occupational therapy as well as its value, which was found to be statistically significant. Conclusions: Productive daily living is incumbent upon a person supported by his or her environment using products to complete daily tasks that facilitate participation. Evidence-based research is needed to demonstrate the distinct value of occupational therapy on design teams.